Neuromuscular profile of handball players during a short-term condensed competition in Brazil - Coelho Rabello Lima, L.; Pignatti Teixeira, I.; Missaki Nakamura, P.; Hayakawa, M. Y.; Oliveira Assumpcao, C.; Pombo Menezes, R. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2015)
The aim of this study was to assess the neuromuscular profile of handball (TH) players during a short-term condensed competition. Nine TH athletes (age: 23 ± 3 years; height: 176.2 ± 10.5 cm; mass: 75.3 ± 8.6 kg) played 5 handball matches in 5 consecutive days and had exercise-induced muscle damage (EIMD) markers such as soreness (SOR), thigh circumference (CIR), knee range of motion (ROM) and countermovement jump height (CMJ) collected before the first match and at the end of each day of competition. Changes over time in these markers were analyzed. Significant changes were found for all EIMD markers assessed. CMJ significantly decreased at the fourth day of competition when compared to baseline (0.41 ± 0.03 m vs. 0.45 ± 0.02 m). ROM decreased on the first day of competition and remained stable until the last day of competition (baseline: 126.5 ± 7.2º; 1st day: 115.8 ± 5.9º; 2nd day: 115 ± 7º; 3rd day: 113.9 ± 8.8º; 4th day: 114.4 ± 8.6º). SOR and CIR were increased at the second day of competition and remained altered thereafter. It was concluded that the characteristics of short-term condensed competition have led TH athletes to significant EIMD. If not avoided, EIMD might lead to reductions in performance in the most important (final) matches.